Involving parents of children treated for cancer in Sweden as public contributors to inform the design and conduct of an evaluation of internet-administered self-help for parents of children treated for cancer: a protocol ... - Woodford, Joanne; Reuther, Christina; Ljungberg, Johan Lars; von Essen, Louise (figshare, 2024)
Abstract Introduction Public contribution in research can facilitate the design and conduct of meaningful research, resulting in feasible and sustainable solutions to healthcare challenges. However, the evidence concerning the acceptability, feasibility, and impact of public contribution in research is limited. We will embed a mixed-method examination of public contribution activities into the CHANGE trial. The overall aim of the CHANGE trial is to evaluate the efficacy and cost-effectiveness of an internet-administered, guided, low-intensity cognitive behavioral therapy-based self-help intervention (EJDeR) plus treatment as usual (TAU) versus TAU for symptoms of depression and/or Generalized Anxiety Disorder in a superiority randomized controlled trial with an internal pilot phase. In this protocol we describe how we aim to: (1) involve parents of children treated for cancer in the managing and undertaking, analysis and interpretation, and dissemination phases of the CHANGE trial; and (2) examine the ...